Penerapan Sistem Produksi Berkelanjutan dalam Pemberdayaan Masyarakat: (Studi Literatur pada Implementasi Teknik Industri di Komunitas Lokal) - Muhamad Noval (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This literature study examines the application of sustainable production systems in community empowerment, particularly focusing on industrial engineering implementation in local communities. Using a qualitative approach through document analysis, focus group discussions, and in-depth interviews, the research identifies three critical findings. First, community-based production system models that integrate contextual analysis, participatory design, and continuous monitoring significantly improve productivity and income of local communities, as demonstrated in the weaving community in Sleman, Indonesia. Second, production engineering interventions that combine technological innovation and social empowerment generate sustainable economic impacts, including 11-13% increase in global agricultural commodity production and 43% reduction in worker idle time in the manufacturing sector. Third, an adaptive conceptual framework connecting local wisdom with digital technology strengthens community resilience, as seen in green construction practices based on local materials that reduce costs by up to 20% while improving quality of life. The study strengthens socio-technical systems theory by demonstrating that the success of sustainable production systems depends on synergies between technical, social, and institutional aspects.